Characterization of Series Iteration Log-periodic Fractal Koch Printed Antenna Equipped with Balun Unit - Achmad Munir; Dida Tuhu Putranto; Heroe Wijanto (Journal of ICT Research and Applications, 2013)
In this paper, characterization of log-periodic fractal Koch antenna in series iteration and equipped with balance-unbalance (balun) unit is investigated numerically and experimentally. The proposed antenna which is deployed an FR-4 Epoxy dielectric substrate using printed-antenna techniques is designed based on Koch fractal geometry in series iteration to minimize its transversal dimension. Since the proposed antenna is a balanced antenna type, then it requires a balun circuit to be available being fed from a coaxial type transmission line. Prior to realization and experimental characterization, some basic antenna parameters including VSWR, impedance characteristic, gain, and radiation pattern are investigated numerically to obtain the optimum architectural design. Moreover, the number of antenna elements as well as the effect of balun unit is also analyzed numerically. From the result, it shows that the proposed antenna has a dimension of 120mm x 150mm, working bandwidth from 0.7GHz"“2.6GHz for VSWR < 2, and overall gain of more than 6dB for frequency range > 1.6GHz.